直齿锥齿轮修形齿面安装误差敏感性分析 - 曹雪梅; 娄佳佳; 马战勇 (Jixie chuandong)
On the basis of establishing the straight bevel gear meshing coordinate system with installation error,the way of using Gauss curvature of different surface to indicate installation error sensitivity of the straight bevel gear modification tooth surface on the two tangent contact tooth surfaces is put forward.The contact path of modification straight bevel gear which has low sensitivity to installation errors is obtained by using penalty function method to optimize the long axis of the contact ellipse. The result shows that contact ellipse long axis have the largest effect on the tooth surface sensitivity coefficient and the better contact path is gained after optimizing the long axis of the contact ellipse,installation errors sensitivity of the straight bevel gear modification tooth surface are able to reduce when contact path is perpendicular to root cone.